2014
DOI: 10.2298/tsci110531026a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of entropy generation in laminar forced convection flow over inclined backward and forward facing steps in a duct under bleeding condition

Abstract: A numerical investigation of entropy generation in laminar forced convection of gas flow over a recess including two inclined backward and forward facing steps in a horizontal duct under bleeding condition is presented. For calculation of entropy generation from the second law of thermodynamics in a forced convection flow, the velocity and temperature distributions are primary needed. For this purpose, the 2-D Cartesian co-ordinate system is used to solve the governing equations which are conservations of mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Figure 10 confirms that for high Reynolds number, the effect of nanoparticle type on average Nusselt number has a minor effect; the smallest values are obtained for the heavier particle, Ag. The analysis of the shape of this curve can confirm, at least qualitatively, that the evolution of Nusselt number versus the volume fraction of nanofluid is consistent with the numerical study of Atashafrooz and colleagues [22].…”
Section: Heat Transfersupporting
confidence: 86%
“…Figure 10 confirms that for high Reynolds number, the effect of nanoparticle type on average Nusselt number has a minor effect; the smallest values are obtained for the heavier particle, Ag. The analysis of the shape of this curve can confirm, at least qualitatively, that the evolution of Nusselt number versus the volume fraction of nanofluid is consistent with the numerical study of Atashafrooz and colleagues [22].…”
Section: Heat Transfersupporting
confidence: 86%
“…Based on the result of grid tests for obtaining the grid-independent solutions, six different meshes were used in the grid independence study. Numerical solutions are obtained iteratively such that iterations are terminated when sum of the absolute residuals is less than 4 …”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Consequently, it has been used in the benchmark investigations. There are many studies about laminar convection flow over BFS in a 2-D duct by several investigators [1]- [4]. Velocity measurements were reported for three-dimensional laminar separated airflow adjacent to a backward-facing step using twocomponent laser Doppler velocimeter by Armaly et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the entrainment coefficients, for elliptical jet case had average values of 0.15 and 0.58. Atashafrooz et al [9] worked on entropy generation in laminar forced convection of gas flow over a recess including two inclined backward and forward facing steps in a horizontal duct under bleeding condition. Other related studies on forward facing step flow can be found in literature [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%